Evaluation of Surgical Treatment by PHILOS Plate versus Conservative Treatment for Displaced Proximal Humeral Fractures in Elderly patients - Hamdy A. Tammam; Elsayed Said; Hossam Hamed; Ahmed Khairy (SVU - International Journal of Medical Sciences)
Background: Proximal humeral fractures account for 5:6% of all adult fractures; according to Neer classification displaced fracture could be two-, three-, and four-part fractures of the proximal humerus. Objectives: This study aims to evaluate surgical treatment outcomes by PHILOS plate versus conservative treatment for displaced humeral fractures in elderly patients. Patients and methods: This was a prospective randomized comparative study that was conducted on a total of 40 patients that fulfilled inclusion criteria presented with displaced proximal humeral fracture randomly selected from those seeking the medical care of the Orthopedic Surgery Department of our institute between 2022 and 2023, managed either by conservative management or by PHILOS plate. Results: Forty patients presented with proximal humerus fracture, twenty in the Conservative treatment group and twenty in the PHILOS group. The PHILOS Plate group showed a highly significant increase in extension over the three visits (p-value < 0.0001*). There was an increase in internal rotation for both the Conservative Treatment group (p-value < 0.0001*) and the PHILOS Plate group (p-value = 0.031*). Conclusion: The conservative treatment group and the PHILOS plate group experienced significant improvements in flexion and internal rotation, with the PHILOS plate group displaying a substantial enhancement in extension and external rotation. The conservative group showed a higher Constant score.